Management of Borderline Ovarian Tumors - Chuenkamon Charakorn (The Royal Thai College of Obstetricians and Gynaecologists, 2018)
Borderline ovarian tumors are similar to the other adnexal masses in terms of clinical presentation. Surgery is the main treatment. Because of the young age of the patients and early stage of diseases at the time of diagnosis, fertility-sparing surgery is favorable. If the intraoperative frozen section reports a borderline tumor, surgical staging should be performed. The surgical staging includes cytologic washing or ascites fluid collection, omentectomy and peritoneal biopsies. The routine lymphadenectomy is not recommended. In terms of fertility-sparing surgery, the unilateral salpingo-oophorectomy is preferred if the other site of ovary is not affected. However, if there are bilateral ovarian involvements, unilateral salpingo-oophorectomy with ovarian cystectomy or bilateral ovarian cystectomy can be considered. The prognostic factors include the stage of disease, the presence of micropapillary in serous tumor, the presence of microinvasion, and the presence of peritoneal implants. Post-operative chemotherapy should be discussed and administrated, similar to the treatment of low grade serous epithelial ovarian cancer if the invasive implantation is detected.